Análise transcriptômica comparativa da infecção por papilomavírus bovino - Barros, Gerlane dos Santos (2018)
Bovine papillomavirus (BPV) is the causative agent of papillomatosis in cattle. The disease causes cutaneous and mucosal lesions that can be minimized or lead to the appearance of malignant tumors. It occurs in Brazil and in several other countries, mainly affecting young animals. In addition to the unpleasant appearance of the animal affected by cutaneous papillomatosis, the problem can cause incalculable damage to the creative differences, especially in regard to the decrease of productivity. Knowing that Brazil is one of the great producers of meat and milk in the world, this study aims to identify possible molecular mechanisms that are behind the pathological processes associated with bovine papillomatosis through the identification of genes related to the development of the lesions. For this, next-generation RNA sequencing was used to assess differentially expressed genes in infected by BPV and non-infected bovines. Three animals with papillomatosis lesion and three without papillomatosis lesion were studied. The Galaxy platform was used to analyze the data generated by the sequencing. The Illumina output files were converted to FASTQ format. Quality evaluation was performed using FastQC and the sequence quality cut was performed using Trimmomatic. TopHat and Bowtie were used to map and align the reads with the reference genome. The abundance of the expressed genes was verified using Cuffilinks. Cuffdiff was used for differential expression analysis. Functional annotation of the differentially expressed genes was performed using Gene Ontology (GO) databases. RNA-sequencing generated a total of 121,722,238 of reads. In the gene expression analysis, a total of 13,421 genes expressed were identified and of these 1343 were differentially expressed. The functional annotation of differentially significant genes showed that many genes presented functions or they were related to metabolic pathways associated with the progression of papillomatosis lesions and cancer development in cattle. Although more studies are needed, this is the first study that focused on a large-scale evaluation of gene expression associated with the BPV infection, which is important to identify possible mechanisms regulated by the host genes that are necessary the development of the lesion.